Lignocelulósicos nos processos de purificação de biodiesel por via úmida utilizando floculantes de fontes renováveis e processo de separação com membranas de celulose regenerada - Ribeiro, Elaine Angélica Mundim (2017)
Biodiesel is purification conventionally using water and dry clean technologies. The former eliminates the remaining water-soluble sodium salts and soaps formed, however can cause large volumes of effluent. Alternatively, the use of membrane technology for the purification of crude biodiesel has provided promising results with less water usage. The main objective of this research is to understand the application of products obtained from lignocellulosic sources in the conventional stages of biodiesel purification (i.e., wet and membrane purification), were considered for the application of products from renewable sources. The treatment of the biodiesel effluent was carried out with laboratory (EFLUL) and industrial (EFLUI) effluents. The synthesized flocculants used were cationic hemicellulose (HC) and cellulose acetate sulfate (SAC), and the commercial flocculants used were cationic tannin (T) and polyacrylamide (PAM), as polyacrylamide being the reference polymer to compare with SAC. Treatment with primary flocculant (i.e., tannin) was effective in equalization pH 12 and flocculation pH 8. The cationic hemicellulose was tested associated with tannin (T/HC) in different proportions and help decrease the volume of sludge and the thermal stability of the sludge, favoring its degradation. In addition, this work also investigated the use of an anionic second polymer (dual-flocculation) (SAC and PAM). The binary floc improved the effluent quality by reducing turbidity from 30 to 40 NTU to 3 to 8 NTU for the EFLUL and from 45 to 56 NTU to 14 to 20 NTU for the EFLUI. Also, the chemical oxygen demand (COD) and total suspended solids (TSS) were reduced (>98%). Thus, due to the high removal provided by the polyelectrolyte system from renewable sources, those are suitable for treatment of biodiesel effluent. Purification of biodiesel using the membrane purification system was performed using membranes of pure regenerated cellulose (M-CR) and silicon dioxide (M-CR-Si) added in the thicknesses of 0.05, 0.08 and 0.10 mm. The membranes produced had an asymmetric structure. The M-CR did not present biodiesel permeate flux due to the reduced porosity caused by the interaction of biodiesel with the cellulose structure. The effect of reducing membrane porosity was attenuated by the addition of silicon dioxide to the polymer solution, which caused increase permeability. The protein rejection, determined with trypsin, showed greater rejection by the membranes that had lower levels of silicon dioxide in their composition (M-CR-Si2-0.05 and M-CR-Si2-0.08). However, the rejections obtained were less than 80% and it was not possible to determine the cut-off point of the membrane. The concentration of glycerin, an important parameter of biodiesel quality, showed 0.026 ± 0.017% and 0.026 ± 0.018% for M-CR-Si2-0.05 and M-CR-Si2-0,08 respectively. Thus, regenerated cellulose membranes with silicon dioxide were promising because they reached levels close to those established by Brazilian legislation, which is 0.02%.